The characterization of a novel magnetic biochar derived from sulfate-reducing sludge and its application for aqueous Cr(Ⅵ) removal through synergistic effects of adsorption and chemical reduction - Chen, Yongjun (2023)
Removal of heavy metals from the aqueous environment via physiochemical adsorption always remains a great challenge owing to the slow kinetics and low removal capacity for the conventional adsorbent. In this study, the sulfate-reducing bacteria (SRB)-rich anaerobic sludge was pyrolyzed for the preparation of magnetic biochar, i.e. SBC-20-500 (SBC: sulfate-reducing sludge-based biochar; 20 denotes the biochar dosage, namely 8 g dried sludge in 400 mL iron solution which is equal to 20 g/L; 500 represents the pyrolysis temperature, i.e. at 500 °C) with tunable pore structure and surface properties towards efficient removal of chromium (Cr (Ⅵ)). The characterization revealed that magnetic biochar SBC-20-500 exhibited higher surface area and larger pore volume compared to non-magnetic SBC-500. Batch experiments on Cr (Ⅵ) removal were performed under different biochar dosages, pH values, initial Cr (Ⅵ) concentrations and temperatures. The results illustrated that magnetic biochar demonstrated much larger Cr (Ⅵ) adsorption capacity with qe of 5.3585 mg/g as compared to non-modified one (qe = 0.7206 mg/g). The maximum Cr (Ⅵ) removal efficiency of SBC-20-500 reached approximately 93.7% within 24 h under the conditions of pH = 3.0, biochar dosage = 0.8 g and initial Cr (Ⅵ) concentration = 50 mg/L. The kinetic and isotherm fitting results suggested that the pseudo-second-order kinetic and Langmuir isotherm model were more suitable for describing the adsorption behavior of Cr (Ⅵ) by SBC-20-500. The XPS and FTIR results confirmed that chemical reduction of Cr (Ⅵ) to Cr (Ⅲ) also played a role in Cr (Ⅵ) removal in the presence of SBC-20-500. Moreover, the Cr (Ⅵ) removal capacity could still achieve 3.50 mg/g even after five adsorption-desorption cycles, indicating the satisfactory reusability of the as-prepared biochar. The results of this study may provide a win-win approach for simultaneous resource recovery from the wasted sulfate-reducing sludge (SRS) and highly-efficient remediation of Cr (Ⅵ)-contaminated environment.